2013
DOI: 10.3989/gya.095312
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid classes and fatty acid composition of ewe’s and goat’s milk

Abstract: RESUMEN Contenido de ácidos grasos de las diferentes clases de fosfolípidos de la leche de oveja y de cabraSe ha analizado el contenido, distribución de las especies individuales y la composición en ácidos grasos de los fosfolípidos (FL) de la leche de oveja y de cabra. Se ha estudiado también la unión de cepas enterotoxigénicas y uropatogénicas de Escherichia coli a estos compuestos y el efecto de los FL sobre la hemaglutinación provocada por estas bacterias mediante inmunodetección en placa y ensayos en plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Similar to other mammalian milk lipids, five major categories of PLs in GMF were identified as PE, PC, SM, PI, and PS. These accounted for more than 90% of the total PLs and PE was with the highest proportion, followed by PC, which was in agreement with the previous studies. ,, However, some researchers observed that PC was predominant in PLs in GMF. ,, This discrepancy might be relevant to factors such as goat breeds and diets. The relative contents of PC and PS were not affected by lactation periods, while PE and PI increased remarkably from goat colostrum to mature milk.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other mammalian milk lipids, five major categories of PLs in GMF were identified as PE, PC, SM, PI, and PS. These accounted for more than 90% of the total PLs and PE was with the highest proportion, followed by PC, which was in agreement with the previous studies. ,, However, some researchers observed that PC was predominant in PLs in GMF. ,, This discrepancy might be relevant to factors such as goat breeds and diets. The relative contents of PC and PS were not affected by lactation periods, while PE and PI increased remarkably from goat colostrum to mature milk.…”
Section: Resultssupporting
confidence: 90%
“…30,43,44 However, some researchers observed that PC was predominant in PLs in GMF. 8,33,45 This discrepancy might be relevant to factors such as goat breeds and diets. The relative contents of PC and PS were not affected by lactation periods, while PE and PI increased remarkably from goat colostrum to mature milk.…”
Section: Fatty Acid Positional Distributionmentioning
confidence: 99%
“…Caprine (Et-Thakafy, Guyomarc'h, andLopez 2017;Russo et al 2013). Ovine (Et-Thakafy, Guyomarc'h, and Lopez 2017;Zancada et al 2013).…”
Section: Milk Fat Globule Formationmentioning
confidence: 99%
“…However, these data have been further updated/completed by the works carried out on small ruminants' milk and some of its products by Yao et al [36], Castro-Gómez et al [37], Zancada et al [38], Contarini and Povolo [39], Rodríguez-Alcalá and Fontecha [40] (this latter also focused on powder buttermilk), and Park [41]. Moreover Barry et al [42] reported the PL composition of butter, butterserum, cream, butteroil, and whole and skimmed milk while Fong et al [43] analysed infant formulas and Ferreiro et al [44] described the evolution of PL concentration during the production of quark cheese.…”
Section: Contents and Distribution Of Polar Lipids In Dairy Productsmentioning
confidence: 99%
“…Regarding the compounds distribution (Table 2), for ewes' it is 26.1–40.0 g GPE/100 g PL, 26.4–27.2 GPC/100 g PL; 4.96–10.7 GPS/100 g PL; 4.16–6.40 GPI/100 g PL; and 22.6–29.7 SM/100 g PL while in goats' milk it has been reported as 19.9–41.4 g GPE/100 g PL; 27.2–31.9 g GPC/100 g PL; 3.2–14 g GPS/100 g PL; 4.00–9.37 g GPI/100 g PL; and 16.1–29.2 g SM/100 g PL. Furthermore, Zancada et al [38] also reported the fatty acid (FA) composition of PL in these milks (Table 3), with palmitic (34% in GPC, 28.8% in GPS, 25.5% in GPI, 12% in GPE, and 25% in SM for ewes' milk; 40% in GPC, 13.3% in GPS + GPI, 21.2% in GPE, and 20.7% in SM for goats' milk), stearic (18% in GPC, 33.9% in GPS, 28.6% in GPI, 17.5% in GPE, and 6.3% in SM for ewes' milk; 8% in GPC, 47.9% in GPS + GPI, 12.4% in GPE, and 8% in SM for goats' milk), and oleic acid (32.3% in GPC, 16.7% in GPS, 25.2% in GPI, 53.6% in GPE, and 0.6% in SM for ewes' milk; 34.4% in GPC, 29.7% in GPS + GPI, 50.6% in GPE, and 0.9% in SM for goats' milk) as the main compounds. On the other hand, for cows' milk these FAs are also the most abundant in the composition of phospholipids: palmitic acid was 35.5% in GPE, 34.7% in GPC, 27.7% in GPS + GPI, and 18.9% in SM while stearic was 16.9% in GPE, 9.5% in GPC, 25.7% in GPS + GPI, and 4.3% in SM and oleic acid, 23.5% in GPE, 26.7% in GPC, 24.9% in GPS + GPI, and 0.5% in SM [45].…”
Section: Contents and Distribution Of Polar Lipids In Dairy Productsmentioning
confidence: 99%